Physiological Roles and Therapeutic Potential of Ca2+ Activated Potassium Channels in the Nervous System - Kshatri, Aravind S.; Gonzalez-Hernandez, Alberto; Giraldez, Teresa (Frontiers in Molecular Neuroscience, 2018)
Within the potassium ion channel family, calcium activated potassium (KCa) channels are unique in their ability to couple intracellular Ca2+ signals to membrane potential variations. KCa channels are diversely distributed throughout the central nervous system and play fundamental roles ranging from regulating neuronal excitability to controlling neurotransmitter release. The physiological versatility of KCa channels is enhanced by alternative splicing and co-assembly with auxiliary subunits, leading to fundamental differences in distribution, subunit composition and pharmacological profiles. Thus, understanding specific KCa channels’ mechanisms in neuronal function is challenging. Based on their single channel conductance, KCa channels are divided into three subtypes: small (SK, 4-14 pS), intermediate (IK, 32-39 pS) and big potassium (BK, 200-300 pS) channels. This review describes the biophysical characteristics of these KCa channels, as well as their physiological roles and pathological implications. In addition, we also discuss the current pharmacological strategies and challenges to target KCa channels for the treatment of various neurological and psychiatric disorders.